(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
This thesis examines the complex relationship between excess weight and reproductive system development in male adolescents. Current evidence demonstrates that overweight status significantly alters hormonal patterns, pubertal timing, and reproductive function through disruption of the hypothalamic-pituitary-gonadal axis. Key findings indicate altered testosterone metabolism, modified pubertal progression, and potential long-term fertility implications. The research underscores the critical importance of weight management during adolescence for optimal reproductive health outcomes.